Application of the finite element method in the analysis of composite materials: A review - Müzel, Sarah David [UNESP]; Bonhin, Eduardo Pires [UNESP]; Guimarães, Nara Miranda [UNESP]; Guidi, Erick Siqueira [UNESP] (MDPI, 2020)
The use of composite materials in several sectors, such as aeronautics and automotive, has been gaining distinction in recent years. However, due to their high costs, as well as unique characteristics, consequences of their heterogeneity, they present challenging gaps to be studied. As a result, the finite element method has been used as a way to analyze composite materials subjected to the most distinctive situations. Therefore, this work aims to approach the modeling of composite materials, focusing on material properties, failure criteria, types of elements and main application sectors. From the modeling point of view, different levels of modeling-micro, meso and macro, are presented. Regarding properties, different mechanical characteristics, theories and constitutive relationships involved to model these materials are presented. The text also discusses the types of elements most commonly used to simulate composites, which are solids, peel, plate and cohesive, as well as the various failure criteria developed and used for the simulation of these materials. In addition, the present article lists the main industrial sectors in which composite material simulation is used, and their gains from it, including aeronautics, aerospace, automotive, naval, energy, civil, sports, manufacturing and even electronics.
Keywords: Anisotropicmaterial; Failure criteria; Multiscale approaches; Orthotropicmaterial; Plate element; Shell element; Transverse isotropicmaterial